2008
DOI: 10.1007/s11274-008-9781-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH, sucrose and ammonium sulphate concentrations on the production of bacterial cellulose (Nata-de-coco) by Acetobacter xylinum

Abstract: The effect of pH, sucrose and ammonium sulphate concentrations on the production of nata-de-coco, a form of bacterial cellulose, by Acetobacter xylinum was studied. Comparisons for physical properties like thickness, wet weight, water-holding capacity (WHC), moisture content and hardness, a textural parameter were done on nata-de-coco grown in tender coconut water medium supplemented with varying concentrations of sucrose and ammonium sulphate at different pH values. The results were analysed by fitting a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 18 publications
2
18
0
3
Order By: Relevance
“…Although A. xylinum 0416 is an acidophilic bacterium, previous studies had demonstrated that too acidic environment (below pH 4.0) can inhibit the bacterial growth and thus end up with lower bacterial cellulose production [5,18]. Similar result was reported by Jagannath who found that bacterial cellulose was absent at pH 3.5 even after 20 days of fermentation [24].…”
Section: Resultssupporting
confidence: 65%
“…Although A. xylinum 0416 is an acidophilic bacterium, previous studies had demonstrated that too acidic environment (below pH 4.0) can inhibit the bacterial growth and thus end up with lower bacterial cellulose production [5,18]. Similar result was reported by Jagannath who found that bacterial cellulose was absent at pH 3.5 even after 20 days of fermentation [24].…”
Section: Resultssupporting
confidence: 65%
“…Nata or bacterial cellulose was prepared as described in our earlier paper (Jagannath, Kalaiselvan, Manjunatha, Raju, & Bawa, 2008;Jagannath, Manjunatha, Ravi, & Raju, in press). A. xylinum (NCIM 2526) culture obtained from National Collection of Industrial Microorganisms (NCIM), National Chemical Laboratory, Pune India was grown under static conditions in modified Hestrin and Schramm medium (Hestrin & Schramm, 1954).…”
Section: Preparation Of Natamentioning
confidence: 99%
“…In coconut water medium, acetic acid was used to bring down the pH as it had a better effect on Acetobacter xylinum 0416 growth compared to other acids [12]. The acetic acid was broken down to carbon dioxide and water which allow more energy generated by bacteria.…”
Section: Resultsmentioning
confidence: 99%